2003
DOI: 10.1128/ec.2.1.34-48.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Sequence Tag Analysis of the Human Pathogen Paracoccidioides brasiliensis Yeast Phase: Identification of Putative Homologues of Candida albicans Virulence and Pathogenicity Genes

Abstract: Paracoccidioides brasiliensis, a thermodimorphic fungus, is the causative agent of the prevalent systemic mycosis in Latin America, paracoccidioidomycosis. We present here a survey of expressed genes in the yeast pathogenic phase of P. brasiliensis. We obtained 13,490 expressed sequence tags from both 5 and 3 ends. Clustering analysis yielded the partial sequences of 4,692 expressed genes that were functionally classified by similarity to known genes. We have identified several Candida albicans virulence and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
0
15

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(194 citation statements)
references
References 68 publications
5
174
0
15
Order By: Relevance
“…Pb14-3-3 expression was evaluated in PbWT, PbEV and Pb14-3-3 aRNA yeast cells; b-tubulin was selected as the endogenous control. 74 The sequences of the oligonucleotide primers used for the amplification of the target gene were Pb14-3-3RT-forward (5 0 -AATCTGCTTTCCGTTGCCTA-3 0 ) and Pb14-3-3RT-reverse (5 0 GTTTTGGCGGTACTCCTTGA-3 0 ), the qRT-PCR product span any of the region targeted by antisense. For the b-tubulin gene, the primer sequences were b-tubulin RT-forward (5 0 -GTGGACCAGGTGATCGATGT-3 0 ) and b-tubulin RT-reverse (5 0 -ACCCTGGAGGCAGTCACA-3 0 ).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Pb14-3-3 expression was evaluated in PbWT, PbEV and Pb14-3-3 aRNA yeast cells; b-tubulin was selected as the endogenous control. 74 The sequences of the oligonucleotide primers used for the amplification of the target gene were Pb14-3-3RT-forward (5 0 -AATCTGCTTTCCGTTGCCTA-3 0 ) and Pb14-3-3RT-reverse (5 0 GTTTTGGCGGTACTCCTTGA-3 0 ), the qRT-PCR product span any of the region targeted by antisense. For the b-tubulin gene, the primer sequences were b-tubulin RT-forward (5 0 -GTGGACCAGGTGATCGATGT-3 0 ) and b-tubulin RT-reverse (5 0 -ACCCTGGAGGCAGTCACA-3 0 ).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…The pyrG used in the A. fumigatus cassette for generating the mutant strains were used as marker for prototrophy and was amplified from pCDA21 plasmid. 56 The DNA fragments together with plasmid linearized pRS426 BamHI/ EcoRI were transformed into S. cerevisiae strain SC9721 (FGSC) by the lithium acetate method 57 and DNA of the transformants extracted as previously described 58 TaKaRa Ex Taq TM DNA Polymerase (Clontech Takara Bio) was used for DNA amplification and Southern blot analyses demonstrated that the transformation cassettes had integrated homologously at the targeted A. fumigatus loci. A. fumigatus transformation was performed as described by de Castro et al 48 The complementing strains were constructed by first isolating from the corresponding deletion strain, a pyrG ¡ auxotroph sector resistant to 0.75 mg/ml of 5-FOA (5-Fluoroorotic acid, Sigma-Aldrich), a fluorinated derivative of the pyrimidine precursor orotic acid.…”
Section: Construction Of the A Fumigatus Mutantsmentioning
confidence: 99%
“…Although a couple of peptides would match those of subtilisins, the number of identical amino acids was not enough to guarantee reliable protein identification. One difficulty to analyze generated peptides is the lack of complete genome information for P. brasiliensis, although there are two GenBank databases of partial translated sequences [19,20]. It is important to point out that there is a 481-amino acid P. brasiliensis subtilase of the S8 family deposited in the GeneBank (Accession number AAP83193).…”
Section: Resultsmentioning
confidence: 99%